(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
This study has focused on the constitutionality of capital punishment, as well as its procedural components, including the concerns and discussions that judges and courts in India have while passing death sentences. Discuss the tenets and arguments put forward by contemporary penology about this matter. We have also been stressing the opinions of several jurists and legal scholars who possess extensive knowledge of both law and society. In order to arrive at the right justification based on relevant legal reasoning, we have also paid close attention to a number of landmark and historic rulings that have changed the current legal position.